Sustained Feelings of Success and Agency: Keys to Literacy Motivation among Adolescents with Learning Disabilities. Issue 1 (1st January 2021) - Louick, Rebecca; Scanlon, David
ABSTRACT: This study explored prior experiences that shaped literacy motivation beliefs among adolescents with learning disabilities (LD). Data included student and teacher interviews, teacher response scales, and classroom observations. Two cycles of analysis, using directed content and thematic approaches, resulted in findings that indicate two types of experiences that were relevant to literacy motivation: a) ones of literacy success, and b) ones providing a sense of agency. Students demonstrated motivation to read, and to accept support, when beliefs in either area made positive contributions to self-perception. However, motivation for both activities was compromised when students faced challenges to positive self-perception. These findings highlight the particular challenges educators face in providing academic services to adolescents who, like their non-LD peers, are developmentally inclined to seek autonomy, and whose self-perceptions as readers and writers can be challenged by accepting supports. Implications could be incorporated into effective literacy interventions for adolescents with LD.